1995
DOI: 10.1259/dmfr.24.2.9515382
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of detailed zonography with periapical radiography for the detection of periapical lesions.

Abstract: The diagnostic accuracy of detailed zonography using the Scanora multimodal X-ray system was compared with that of periapical radiography. The study was based on the detection of periapical bone lesions at 259 dental sites distributed evenly throughout the dentitions of 164 patients. Each site was examined by periapical radiography and zonography, in parallel. The zonograms consisted of four detailed images that could also be read as stereopairs, in either the horizontal or vertical direction. Five observers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Differences in overall sensitivities between detailed tomography and DNBR [11][12] and DZ [20][21][22] were minor. Sensitivities with tomography for periapical lesions in the mandibular premolar and molar regions were lower than those of DNBR 11 and DZ 2 ".…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Differences in overall sensitivities between detailed tomography and DNBR [11][12] and DZ [20][21][22] were minor. Sensitivities with tomography for periapical lesions in the mandibular premolar and molar regions were lower than those of DNBR 11 and DZ 2 ".…”
Section: Discussionmentioning
confidence: 89%
“…However, in clinical studies, this is not always possible for practical and ethical reasons [20][21][22] . Because we could not know the actual state of the patients in this study, we evaluated the diagnostic ability of detailed tomography by comparing it with that of periapical radiography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8). It has been demonstrated that the visualization of periapical bone lesions, particularly in the premolar and molar regions, is better than that achieved with intraoral periapical radiography (7). Not surprisingly, differences between those techniques were smaller for lesions in the anterior jaw regions.…”
Section: Conventional Tomographymentioning
confidence: 99%